Emerging Blockchain Integrated E-Commerce using Django (International Journal of Scientific Research in Science and Technology, 2024)
In today's digital age, e-commerce has revolutionized the way people shop, offering unparalleled convenience and a vast selection of products and services. However, this rapid growth has brought its own set of challenges, including security concerns, transparency issues, and inefficiencies in transaction processes. Blockchain technology, with its decentralized, transparent, and secure nature, offers a promising solution to many of these challenges. This project explores the integration of blockchain technology into e-commerce platforms, aiming to enhance security, transparency, efficiency, and user trust. Blockchain technology has the potential to improve e commerce transactions by reducing payment disputes, chargebacks, fraud, and lack of transparency. Blockchain technology enables safe digital asset storage and sharing over a decentralised network. This allows customers to obtain product data, including origin and supplier, and reduces the danger of fraud. The primary objective of this project is to develop and implement a blockchain integrated e-commerce platform that leverages the unique advantages of blockchain technology to address the inherent limitations and challenges of traditional E- commerce systems. Finally, the paper aims to create a more secure, transparent, efficient, and user-centric online shopping experience.
Keywords: Blockchain; E-commerce; Decentralized; Django; Ledger; Transactions